2005
DOI: 10.1086/496927
|View full text |Cite
|
Sign up to set email alerts
|

Galactomannan and Computed Tomography-Based Preemptive Antifungal Therapy in Neutropenic Patients at High Risk for Invasive Fungal Infection: A Prospective Feasibility Study

Abstract: Preemptive therapy based on enzyme immunoassay and HRCT reduced the exposure to expensive and potentially toxic drugs and offered effective antifungal control, but it failed to detect non-Aspergillus IFI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
400
5
18

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 544 publications
(431 citation statements)
references
References 42 publications
8
400
5
18
Order By: Relevance
“…These patients are admitted to the hospital during their period at high risk, and GM monitoring is recommended every 3-4 days. 11,12 A diagnosis-driven strategy that incorporates prospective GM monitoring should be combined with highresolution computed tomography imaging, and appropriate clinical and microbiological evaluation. 11,12 A single positive GM index of X0.7 or two consecutive samples of X0.5 should prompt a diagnostic work-up.…”
Section: Galactomannan (Gm)mentioning
confidence: 99%
See 1 more Smart Citation
“…These patients are admitted to the hospital during their period at high risk, and GM monitoring is recommended every 3-4 days. 11,12 A diagnosis-driven strategy that incorporates prospective GM monitoring should be combined with highresolution computed tomography imaging, and appropriate clinical and microbiological evaluation. 11,12 A single positive GM index of X0.7 or two consecutive samples of X0.5 should prompt a diagnostic work-up.…”
Section: Galactomannan (Gm)mentioning
confidence: 99%
“…11,12 A diagnosis-driven strategy that incorporates prospective GM monitoring should be combined with highresolution computed tomography imaging, and appropriate clinical and microbiological evaluation. 11,12 A single positive GM index of X0.7 or two consecutive samples of X0.5 should prompt a diagnostic work-up. 13 GM monitoring can be continued after antifungal therapy has been initiated.…”
Section: Galactomannan (Gm)mentioning
confidence: 99%
“…This strategy has been evaluated in patients with hematologic malignancies undergoing intensive chemotherapy, but not in allogeneic HSCT recipients. A pilot trial showed a substantial decrease in the use of antifungal drugs compared with the empiric strategy [18]. More recently, a randomized, prospective trial comparing pre-emptive and empiric strategies, mostly in patients with acute leukemia and neutropenia, showed that the former strategy led to increased diagnosis of IFI, no increased mortality, and decreased antifungal drug cost [19].…”
Section: Pre-emptive Therapymentioning
confidence: 99%
“…26 Only patients with ≥ 2 positive serum galactomannan assays or CT and or bronchoscopic evidence for mould infection received antifungal therapy. A total of 41 of 117 febrile neutropenic episodes (35%) had persistent neutropenic fever; however, only 9 patients (22% of the 41 persistent neutropenic fevers; 8% of the original febrile neutropenic episodes) satisfied the pre-defined criteria for antifungal therapy-a 78% relative risk reduction in antifungal therapy use.…”
Section: Pre-emptive Antifungal Therapymentioning
confidence: 99%